Answer: see proof below
Explanation:
Given: A + B + C = π → C = π - (A + B)
→ sin C = sin(π - (A + B)) cos C = sin(π - (A + B))
→ sin C = sin (A + B) cos C = - cos(A + B)
Use the following Sum to Product Identity:
sin A + sin B = 2 cos[(A + B)/2] · sin [(A - B)/2]
cos A + cos B = 2 cos[(A + B)/2] · cos [(A - B)/2]
Use the following Double Angle Identity:
sin 2A = 2 sin A · cos A
Proof LHS → RHS
LHS: (sin 2A + sin 2B) + sin 2C




![\text{Factor:}\qquad \qquad \qquad 2\sin C\cdot [\cos (A-B)+\cos (A+B)]](https://img.qammunity.org/2021/formulas/mathematics/high-school/4e1w8nq8fz45gtimsa92qdhzadwlvkjx18.png)


LHS = RHS: 4 cos A · cos B · sin C = 4 cos A · cos B · sin C
